Optimizing electric vehicle charger installation on a non-urban highway: a case study of BR-386, Motiva Viasul, Brazil - Teixeira, Tiago de Oliveira Mafra; Garcia, Reinaldo Crispiniano (Brazilian Journal of Production Engineering, 2026)
This study aims to find optimal points to place electric vehicle chargers (EVCs) for electric vehicles (EVs) on the non-urban highway BR-386, part of the MOTIVA ViaSul concession. This work applies a Genetic Algorithm (GA) model combined with the Geographic Information System (GIS) to determine the optimal locations of the charging station. The work was implemented in three stages. The first stage is the acquisition and cleaning of the database because the data is obtained from several different sources. The second stage is the implementation of the GA model. This phase uses the applied data, including traffic flow (both in 2025 and an estimate for 2030), electrical energy infrastructure and EV specifications. The third stage is the application of different scenarios to obtain the optimal solution for the model. The model found two optimal locations for EV charger allocation, besides to the ideal number of chargers, the average queue size, and utilization percentage of the chargers depending on the scenario, either the 2025 one or the 2030 scenario.